The surgical treatment of choice for hydatic cyst on the posterior aspect of the liver: diagnostic value of scintigraphy - Puig, Roberto; Rubio, Roberto; Touya (h), Juan José (Cirugía del Uruguay, 2021)
The paper presents a case of a small non-complicated hydatid cyst in the posterior face of the right lobe of the liver. It stresses the importance and need of utilizing liver gammagraphy in all hydatid patients in arder to arrive at an early diagnosis and establish the exact topography of these lesions. It indicates the treatment considered as selective by reason of the moment when it was applied, the approach used and the surgery, which was performed according to Posadas' method.